2020
DOI: 10.7717/peerj-cs.331
|View full text |Cite
|
Sign up to set email alerts
|

Latent based temporal optimization approach for improving the performance of collaborative filtering

Abstract: Recommendation systems suggest peculiar products to customers based on their past ratings, preferences, and interests. These systems typically utilize collaborative filtering (CF) to analyze customers’ ratings for products within the rating matrix. CF suffers from the sparsity problem because a large number of rating grades are not accurately determined. Various prediction approaches have been used to solve this problem by learning its latent and temporal factors. A few other challenges such as latent feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…BFOA is one of the efficient optimisation algorithms that have been used in improving the prediction performance of the CF technique in some recommendation systems ( Al-Hadi et al, 2020b , 2017 ). Accordingly, BFOA is utilized in the ReComS++ approach for reducing the overfitted prediction values by learning the latent features of the neighbours within each cluster.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…BFOA is one of the efficient optimisation algorithms that have been used in improving the prediction performance of the CF technique in some recommendation systems ( Al-Hadi et al, 2020b , 2017 ). Accordingly, BFOA is utilized in the ReComS++ approach for reducing the overfitted prediction values by learning the latent features of the neighbours within each cluster.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…This function provides the correlation between the target record (of game and movement) and total records. The similarity functions that apply the CF technique are Cosine Similarity ( Al-Hadi et al, 2020b ) and the Pearson Correlation Coefficient ( Srifi et al, 2020 ). Note that when using the Cosine or Correlation coefficient for MIRA data, these functions generate some outliers due to the existence of zeros in the feature matrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing social media comments using NLP, the study identified triggers for the Amazon effect, highlighting widespread dissatisfaction and reduced satisfaction with other retailers influenced by elevated consumer expectations shaped by Amazon [158]. The study on CF recommendation systems utilized sentiment analysis on user reviews to derive implicit ratings, introducing novel approaches that demonstrated effectiveness in enhancing CF performance [159].…”
Section: Marketing and Brand Managementmentioning
confidence: 99%
“…Explored the impact of the 'Amazon effect' on consumer perceptions of service attributes in Italian consumer electronics retailers. [159] Amazon, Yelp Introduced CF methods leveraging sentiment analysis on user reviews. [160] Amazon Introduced a novel TADO model for review-based recommender systems.…”
Section: Ref Yearmentioning
confidence: 99%